A comparative analysis on remote user authentication schemes in telemedical healthcare systems. (10th August 2022) - Dewan, Charul; Kumar, T. Ganesh; Gupta, Sunil
In today's era, the e-healthcare sector is emerging and in high demand that provides mobility to the users. It is a system where we put the information at a remote server for access to users and doctors. To access these servers and the data, we need a secure authentication schemes for authentic access to the remote server. Many authentication schemes have been proposed for authentic access to the telemedical remote server. The purpose of this paper is to analyse various telemedical related authentication schemes extensively. The paper addresses the computational cost and energy of various scheme that help to find the security scheme with efficiency. The paper analyses these proposed authentication schemes and they are secure against malicious attacks. The time complexity and energy consumption helps the researcher to work on further design and implementation of authentication schemes.